Proceedings of the 9th International Conference on the Internet of Things 2019
DOI: 10.1145/3365871.3365901
|View full text |Cite
|
Sign up to set email alerts
|

Escaping the Streetlight Effect

Abstract: The integration of systems of autonomous agents in Web of Things (WoT) environments is a promising approach to provide and distribute intelligence in world-wide pervasive systems. A central problem then is to enable autonomous agents to discover heterogeneous resources in large-scale, dynamic WoT environments. This is true in particular if an environment relies on open-standards and evolves rapidly requiring agents to adapt their behavior to achieve their goals. To this end, we developed a search engine for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Where such information is supplied by a service provider, this can be rendered as RDF triples to provide the SPARQL microservice's description. Bienz et al [22] have demonstrated the use of SPARQL endpoints to provide approximate search capabilities for physical devices, seeded from published WoT TDs.…”
Section: Related Workmentioning
confidence: 99%
“…Where such information is supplied by a service provider, this can be rendered as RDF triples to provide the SPARQL microservice's description. Bienz et al [22] have demonstrated the use of SPARQL endpoints to provide approximate search capabilities for physical devices, seeded from published WoT TDs.…”
Section: Related Workmentioning
confidence: 99%
“…The hypermedia environments are pervasive in two fundamental ways: (i) they provide DCs with uniform access to devices in their physical environment, and (ii) they pervade all application areas-since the Web provides a flexible underpinning that can interconnect all these pervasive hypermedia environments in one worldwide system. DC can then navigate the Web (individually or using hypermedia search engines [3]) to discover and interact with digital services, devices, people, other agents, or any other resources on the Web. In addition to uniform access, pervasive hypermedia environments can also be designed and programmed to support interaction, coordination, and stigmergy among people and DCs (see also [4]), or they can act as shared knowledge repositories-e.g., a place where both people and DCs can create and share Web annotations [5].…”
Section: Bringing Digital Companions To the Webmentioning
confidence: 99%
“…See also the Dagstuhl Seminar on Autonomous Agents on the Web (to be held on February 14-19, 2021): https://www.dagstuhl.de/en/program/calendar/ semhp/?semnr=21072 3. At the First International Conference on the World Wide Web (1994), Sir Tim Berners-Lee was noting that documents on the Web describe real objects and relationships among them, and if the semantics of these objects are represented explicitly then machines can browse through and manipulate reality: https://videos.cern.ch/record/2671957…”
mentioning
confidence: 99%